Shadows Between Gesture and Code: Tactile Visuality and Digital Scenographic Critique in Nalini Malani (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This article offers a theoretical analysis of Nalini Malani’s video installations based on the dual meaning of the term “digital”: both as audiovisual technology (light and image projection) and as manual trace (dactylic gesture). The research is structured around three main axes: (1) the visual densification generated by the interplay of projected light, shadow, and pictorial gesture, producing a mobile and stratified visuality; (2) narrative fragmentation and its rhizomatic spatial unfolding, in dialogue with non-Western visual genealogies; and (3) the inscription of the body as rhythm and perceptual intensity, in tension with the ideal of transparency commonly associated with the digital. The study incorporates 3D visualizations of key works to clarify the scenographic structure and explores the critical implications of the shadow as a visual and political operator. Drawing on a transversal approach that combines formal analysis, image theory, and non-hegemonic epistemologies, the article argues that Malani’s practice articulates an alternative model of digital scenography—one in which light, shadow, and body interweave an immersive, fragmentary, and critical experience, challenging the logics of spectacularity and transparency that dominate contemporary digital visuality.
Keywords: Digital scenography; Nalini Malani; shadow; non-linear narrativity; tactile digitality